The injury mechanisms and injury pyramids among children and adolescents in Zhuhai City, China - Xiling Yin; Wencan Dai; Yukai Du; Deyun Li (BMC, 2021)
Abstract Background The unclear mechanisms and severity of injuries in the injury pyramids for Chinese children and adolescents prevent the prioritization of interventions. This study aimed to describe the injury mechanisms and injury pyramids in this population to provide a priority for injury prevention strategies. Methods Death, hospitalization, and outpatient/emergency department visit data from patients aged 0 ~ 17 years with injuries were obtained from January 1, 2013, to December 31, 2017, in Zhuhai City, China. The injury mechanism ratios were calculated, and the injury pyramid ratios were drawn in proportion using injury mortality and the incidence of both injury hospitalizations and outpatient/emergency department injury visits. Results The top three mechanisms for injuries in children and adolescents treated in outpatient/emergency departments were falls (52.02%), animal bites (14.57%), and blunt injuries (10.60%). The top three mechanisms for injury hospitalizations were falls (37.33%), road traffic injuries (17.87%), and fire/burns (14.29%), while the top three mechanisms for injury deaths were drowning (32.91%), road traffic injuries (20.25%) and falls (13.92%). The incidence rate of outpatient/emergency department injury visits for children and adolescents was 11,210.87/100,000; the incidence rate of injury hospitalization was 627.09/100,000, and the injury death rate was 10.70/100,000. For each injury death, there were 59 injury hospitalizations and 1048 outpatient/emergency injury visits. Conclusions The injury mechanisms were different for injury-related outpatient/emergency department visits, hospitalizations, and deaths among children and adolescents. The injury mechanisms by sex at different stages of child development, and interventions should be formulated based on this finding. The ratios of the injury pyramids varied by age, sex, region, and injury mechanisms; minor nonfatal injuries were more common in children and adolescents. The differences in the severity and extent of the injuries suggested that injury interventions in children and adolescents still have a long way to go.